A History of Pergamum : Beyond Hellenistic Kingship - Evans, Richard (Criminal Practice Ser, 2012)
List of Illustrations -- Acknowledgements -- Abbreviations -- Preface -- General Introduction: Some Historical Perspectives -- Chapter 1: A Beginning and an End -- Chapter 2: The Ally of Rome -- Chapter 3: Old and New Horizons -- Chapter 4: Ruler Cults and Physicians -- Chapter 5: The Journey East and a New World -- Chapter 6: Images of a City -- Appendices -- 1. The Attalid Dynasty -- 2. The Kings of Bithynia, Pontus and Cappadocia -- 3. Proconsuls of Asia under the Republic (133-31 BC) -- 4. Proconsuls of Asia in the Early Principate (31 BC-AD 161) -- 5. The Cities of Asia -- Notes -- Select Bibliography -- Index.